(3PgGH GdcSha hfaj GdXdeGA aj Yde GdWH hGdWHGFY hGdMceIs - (3YHO Gddg Hf YRhR GdeQGcTj GdShSj SjOj Hdg, CHh eMeOs
(3ChdgG (B:s
(3gPG cJGH PgGH GdcSha hfai GdXdeGJ hJUfja hHYO (B: (3abO ENJdL UOQi deG fMf HSHjd cTag ef eYGfi GdWH hGdWHGFY hGdMceI , aJefjJ Gf CUf gPG GdcJGH aj Pdc s
(3BNQgG (B:s
(3MH GdQTGO jPgH GdbhHI hGdKCdhd hGdMceI hGdHgb GdCShO hgfG bO GfJgi gPG GdcJGH GdeHGQc s
(3fSNI KGfjIs
(3hHgG HJQ ai GdhQbI (B41s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B987 s
Keywords: (3GdWHs